The Homes Front: The Accommodation Crisis in Halifax, 1941-1951 - White, Jay (Urban History Review / Revue d'histoire urbaine, 1992)
No city in Canada was closer to the front lines of battle in 1942 than Halifax, Nova Scotia. But Halifax, like the rest of the country, was unprepared for a long war and the city struggled to cope with the heavy demand placed on her housing stock and municipal services. In one respect, Halifax was ready: the massive federal investment in new piers and rail facilities, begun before the First World War, enabled the port to accommodate huge British battleships and passenger liners converted into troopships. Her commodious harbour provided safe haven from German U-boats to hundreds of Allied merchantmen. But on the domestic front, Halifax could not even begin to manage the effects of a 10% rise in population in less than two years. Few industrial jobs, limited housing construction, a very high transient population, and a reluctance on the part of the federal government to accept responsibility for local problems all contributed to Halifax having a "rather uncomfortable rail seat at the spectacle of war."— Quotation from "Gateway to the World", film produced by the Nova Scotia Department of Industry and Publicity, 1946.